Associations of short-term PM2.5 exposures with nasal oxidative stress, inflammation and lung function impairment and modification by GSTT1-null genotype: A panel study of the retired adults. (15th September 2021) - Sun, Beibei; Song, Jie; Wang, Ya; Jiang, Jing; An, Zhen; Li, Juan; Zhang, Yange; Wang, Gui; Li, Huijun; Alexis, Neil E.; Jaspers, Ilona; Wu, Weidong
Abstract: PM2.5 (particulate matter ≤2.5 μm in aerodynamic diameter) is a major urban air pollutant worldwide. Its effects on the respiratory system of the susceptible population have been less characterized. This study aimed to estimate the association of short-term PM2.5 exposure with respiratory outcomes of the retired adults, and to examine whether these associations were stronger among the subjects with GSTT- null genotype. 32 healthy subjects (55–77 years) were recruited for five follow-up examinations. Ambient concentrations of PM2.5 were monitored consecutively for 7 days prior to physical examination. Pulmonary outcomes including forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ), peak expiratory flow (PEF), and fractional exhaled nitric oxide (FeNO), and nasal fluid concentrations of 8-epi-prostaglandin F2 alpha (8-epi-PGF2α), tumor necrosis factor-α (TNF-α), interleukin-8 (IL-8) and IL-1β were measured. A linear mixed-effect model was introduced to evaluate the associations of PM2.5 concentrations with respiratory outcomes. Additionally, GSTT1 genotype-based stratification was performed to characterize modification on PM2.5 -related respiratory outcomes. We found that a 10 μg/m 3 increase in PM2.5 was associated with decreases of 0.52 L (95% confidence interval [CI]: -1.04, -0.002), 0.64 L (95% CI: -1.13, -0.16), 0.1 (95% CI: -0.23, 0.04) and 2.87 L/s (95% CI: -5.09, -0.64) in FVC, FEV1, FEV1 /FVC ratio and PEF at lag 2, respectively. Meanwhile, marked increases of 80.82% (95% CI: 5.13%, 156.50%) in IL-8, 77.14% (95% CI: 1.88%, 152.40%) in IL-1β and 67.87% (95% CI: 14.85%, 120.88%) in 8-epi-PGF2α were observed as PM2.5 concentration increased by 10 μg/m 3 at lag 2. Notably, PM2.5 -associated decreases in FVC and PEF and increase in FeNO were stronger among the subjects with GSTT1 -null genotype. In summary, short-term exposure to PM2.5 is associated with nasal inflammation, oxidative stress and lung function reduction in the retired subjects. Lung function reduction and inflammation are stronger among the subjects with GSTT1 -null genotype. Graphical abstract: Image 1 Highlights: Exposure to PM2.5 is associated with nasal oxidative stress and inflammation. Exposure to PM2.5 is associated with lung function reduction and inflammation. GSTT1-null genotype is associated with stronger adverse effects of PM2.5 in lungs.